Fire safety in railway and metro tunnels - Radziszewska-Wolińska, Jolanta Maria (Archives of Civil Engineering, 2026)
The article presents the development of tunnel infrastructure in the world. Then, the hazards occurring in fires occurring in underground rail transport are characterized and several incidents that have occurred are described. It is also noted that a large role in improving fire safety in tunnels is played by conclusions drawn from experience from incidents that have occurred and by predicting new threats and possibilities of preventing them. Despite equipping tunnels with increasingly modern safety systems, fires, accidents and disasters still occur, as is shown by the given number of fires in tunnels in German-speaking countries that occurred in the years 2013–2023. In addition, the article discusses the current EU requirements aimed at ensuring an optimal level of safety in tunnels in the most economical way. They were developed taking into account scenarios of the most probable events. Ensuring that residual risk is reduced to a low level requires combining all safety layers in the following order: prevention, mitigation, evacuation and rescue. It was also emphasized that the proper selection of non-metallic materials for the construction and equipment of rolling stock and tunnel infrastructure is an important element of effective fire protection. Nevertheless, the required systematic inspections of the condition of vehicle and tunnel equipment, as well as rescue operations exercises according to various scenarios provided for in the Tunnel Emergency Plan, play an important role.